Impact of hip and/or knee osteoarthrosis on quality of life: Kakovost življenja bolnikov z artrozo kolkov ali/in kolen - Kravos, Andrej; Jerman, Marta (Acta Medico-Biotechnica, 2021)
Purpose: Osteoarthritis is a chronic degenerative joint disease which has a significant impact on those with osteoarthritis. Osteoarthritis is the most common joint disease, and the prevalence increases with age. After cardiovascular diseases, osteoarthritis is the second most common cause of disability in developed countries. During the last few decades, questionnaires for health–related quality of life have been developed, which are important indicators of the outcomes of treatment of chronic diseases and are also predictors of mortality rates. The COOP/WONCA chart is a valid and reliable questionnaire which is easy to use and useful in family medicine practice.Methods: The cross–sectional study evaluated the effect of hip and/or knee osteoarthritis on the quality of life. The patients included in our random sample were registered in GP surgery with radiologically confirmed disease. Data were collected on patient age and gender, work or job, associated diseases, frequency and type of exercise, and treatment and self–treatment of osteoarthritis. Each patient completed the COOP questionnaire. We analyzed different aspects of quality of life and the associationswith patient characteristics.Results: One hundred fifty–five patients were enrolled and 131.patients returned the questionnaire. Patients had osteoarthritis involving the knee more often than osteoarthritis of the hip. Men underwent regular physical activity more often than women (p = 0.049). Women treated osteoarthritis more often than men (p = 0.038). Of the 155 patients, 43.5% had a moderate quality of life (score = 3), 46.6% had a poor quality of life (score = 4 and 5), and only 1.5% had a good quality of life (score = 1 and 2). Patients reported difficulty with physical fitness and overall health. The quality of life was worse in women, patients in the higher age groups, patients with limited or no physical activity, patients with involvement of more joints, and in patients with co–morbidities (except co–existing cardiovascular disease).Conclusion: Patients with osteoarthritis of the hip and/or knee have a poor quality of life; specifically, such patientshave the greatest difficulty in engaging in physicalactivity and less social activity.
Keywords: osteoarthritis; quality of life; family medicine